Marketing em odontologia - Natali, Filipe Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The market of work in all the areas is if becoming each more competitive time, what it takes the professionals to search different strategies to guarantee its insertion and its space using mainly the marketing tools. Currently, marketing is an area on the rise and is defined as the study of business, starting from the knowledge of the needs and psychology of consumer demand to drive production adapting it to the best market. For the professional success of the surgeon-dentist it is important that it is a good physician, who has a good academic-scientific formation, as well as being a good manager, with formation in the area of administration, marketing, human resources, amongst others. The marketing tools can assist the professionals in the captation and maintenance of patients, divulging its name and its abilities, thus facilitating its insertion in the work market. The objective of this study will be to evaluate the pertinent tools of marketing for use in the area of Odontologia. We performed a literature search by consulting the major databases and consulted official documents of the CFO. There are many tools being used to attract customers, but it can be concluded that the relationship marketing and advertising has long been very effective in winning new clients

O mercado de trabalho em todas as áreas está se tornando cada vez mais competitivo, o que leva os profissionais a buscarem diferentes estratégias para garantir sua inserção e seu espaço utilizando principalmente as ferramentas de marketing. Atualmente, o marketing é uma área em ascensão e é definido como o estudo das atividades comerciais, que partindo do conhecimento das necessidades e da psicologia do consumidor, procura dirigir a produção adaptando-a ao melhor mercado. Para o sucesso profissional do Cirurgião-Dentista é importante que ele seja um bom clínico, que tenha uma boa formação acadêmico-científica, bem como ser um bom gestor, com formação na área de administração, marketing, recursos humanos, dentre outros. As ferramentas de marketing podem auxiliar os profissionais na captação e manutenção de pacientes, divulgando o seu nome e suas habilidades, facilitando assim sua inserção no mercado de trabalho. O objetivo deste estudo foi avaliar as ferramentas de marketing pertinentes para uso na área de Odontologia. Foi realizada uma pesquisa bibliográfica por meio de consulta das principais bases de dados e consultados os documentos oficiais do CFO. Existem inúmeras ferramentas que estão sendo utilizadas para atrair a clientela, mas pode-se concluir que o marketing de relacionamento e a propaganda tem muito sido muito eficientes na conquista de novos pacientes
Keywords: Marketing; Marketing de serviços de saúde; Odontologia; Propaganda